Keanekaragaman Ektoparasit pada Kelelawar Subordo Microchiroptera di Goa Jepang Bukit Plawangan, Sleman, Yogyakarta - Poerwanto, Soenarwan Hery; Ridhwan, Luqman Rasyid; Giyantolin, Giyantolin; Ginawati, Dhea; Paramitha, Desak Putu Raka (Jurnal Veteriner; Vol 21 No 4 (2020), 2020)
Ectoparasites in bats can cause a decrease in health and can be a disease vector. Ectoparasites found in bats are generally members of the Insect Class and Arachnida Class. This study was aim to determine the diversity of ectoparasites in bats of the Microchiroptera suborder in Jepang Cave, Plawangan Hill, Sleman, Yogyakarta and knowing various factors that influence the existence of these ectoparasites in bats. Catching bats is done by mist net, bats are anesthetized and morphometric measurements are carried out. Descriptive methods are used to identify bats and their ectoparasites and analyze the abundance of ectoparasites using prevalence and intensity. Identification of ectoparasites were carried out in the Animal Systematic Laboratory of the Parasitology Section of the Faculty of Biology, Universitas Gadjah Mada, by using the book of ectoparasites identification. Bat species were ound include Miniopterus schreibersii and Rhinolopus pusillus . The results showed that ectoparasite species were found in the bats of the Microchiroptera Suborder from the Subclass Acarina and the Insect Class. The species of Subclass Acarina found were Periglischrus sp., Spinturnix plecotinus, Blattisocius sp., And Glycyphagus sp. Species of the Insect Class found include Megastrebla sp., Stylidia caudata , Basilia sp., and  Brachytarsina sp. The prevalence of R. pussilus in Jepang Cave, was 66.67% and it is frequent. The ectoparasite intensity category of Periglischrus sp. was 0.72, meanwhile Glycyphagus sp. and Stylidia caudata were 0.06, which is very low.